5-Star Programming and Services for Your 55+ Library Customers. - Mates, Barbara T. (ALA Editions, 2003)
As members of the population approach age fifty-five and above, libraries are faced with an untapped opportunity to serve a consistently underserved population. As she explains the ins and outs of planning, developing, marketing, and funding successful programs and services to the graying population, longtime outreach and access advocate Barbara T. Mates demonstrates how libraries can benefit from providing top-notch programs and services for older adults. The latest in the ALA Programming Guides series, this comprehensive resource gets to the heart of what seniors need and wantfrom continuin.